ANALISIS MANAJEMEN “WAKTU” PADA USAHA PENANGKAPAN IKAN TUNA/CAKALANG DENGAN SISTEM RUMPON DI KAWASAN TIMUR PERAIRAN INDONESIA - Bambang Winarso (Jurnal Ilmiah Binaniaga, 2005)
Planning from each activity specially in arrest of fish through of rumpon system always related problem of time allocation and requirement, expense and energy, when operate for arrest started, when have to arrive at schema to take gudgeon and when should have arrived at rumpon to fishing of fish how big expense which must be released, how big labour in concerned in it and others. This study specificly try to see and analyse requirement of required time in the effort arrest of tuna's/cakalang fish by using appliance catch Pool & Line. Which event perceived by activity of arrest since preparation up to moment landing of fish. Note requirement of time from each event represent empirical data to be ana-lysed. Research in territorial of Banda Sea. Result of analysis indicate that from every activity of arrest most time allocation to every activity basically represent critical duration which require to be strived be achieved as precise as possible. Considering arrest of tuna's / cakalang fish by using rumpon mount its efficacy very determined by accuracy of moment time, hence effort to depress time variance in each event will ever strived.